Dialektika Kecerdasan Buatan dan Akal Manusia: Tinjauan Kritis Epistemologi Pendidikan Ibnu Khaldun - Lhegina, Assyifa Qori; Maulaya, Rosendah Dwi (Taklim : Jurnal Pendidikan Agama Islam, 2025)
AbstractThe massive integration of Generative Artificial Intelligence (AI) into the educational landscape has sparked an ontological crisis regarding the erosion of human cognitive autonomy. The instant convenience offered by algorithms threatens to distort the essence of learning from character formation into mere information transaction. This study aims to reconstruct Ibn Khaldun’s educational epistemology, specifically the concepts of Al-Fikr (thinking faculty) and Malakah (habit), as a critical framework to address the phenomenon of AI-induced cognitive offloading. Employing a qualitative approach with philosophical content analysis, this research juxtaposes the text of Al-Muqaddimah against contemporary literature on the psychological impacts of technology. The findings reveal a fundamental contradiction: while AI operates efficiently at the level of Al-‘Aql Al-Tamyizi (discriminative intellect), it lacks the capacity for Al-‘Aql Al-Tajribi (experimental intellect) and Al-‘Aql Al-Nazhari (speculative intellect), which require social embodiment and metaphysical reflection. The study concludes that the "instant culture" of AI is antithetical to the formation of Malakah. Consequently, preserving intellectual authenticity requires the implementation of At-Tadarruj (gradualism) and Munazharah (dialectics), alongside a shift in assessment orientation from product-based to process-based evaluation to prevent human cognitive atrophy.Keywords: Ibn Khaldun, Artificial Intelligence (AI), Islamic Education, Malakah, Cognitive Atrophy.AbstrakIntegrasi masif Generative Artificial Intelligence (AI) dalam lanskap pendidikan telah memicu krisis ontologis mengenai erosi otonomi kognitif manusia. Kemudahan instan yang ditawarkan algoritma berpotensi mendistorsi hakikat belajar dari proses pembentukan karakter menjadi sekadar transaksi informasi. Penelitian ini bertujuan untuk merekonstruksi epistemologi pendidikan Ibnu Khaldun, khususnya konsep Al-Fikr (kemampuan berpikir) dan Malakah (habitus), sebagai kerangka kritis untuk merespons fenomena cognitive offloading akibat ketergantungan pada AI. Menggunakan pendekatan kualitatif dengan metode analisis konten filosofis, penelitian ini mengonfrontasi teks Al-Muqaddimah dengan literatur kontemporer mengenai dampak psikologis teknologi. Temuan penelitian mengungkapkan adanya kontradiksi fundamental: AI beroperasi secara efisien pada level Al-‘Aql Al-Tamyizi (akal pemilah), namun gagal mencapai Al-‘Aql Al-Tajribi (akal eksperimental) dan Al-‘Aql Al-Nazhari (akal spekulatif) yang mensyaratkan pengalaman sosial dan refleksi metafisik. Penelitian ini menyimpulkan bahwa budaya instan AI merupakan antitesis bagi pembentukan Malakah. Oleh karena itu, preservasi otentisitas intelektual menuntut penerapan prinsip At-Tadarruj (gradualisme) dan Munazharah (dialektika), serta pergeseran orientasi evaluasi pendidikan dari berbasis produk (output) menjadi berbasis proses untuk mencegah stagnasi nalar manusia. Kata kunci : Ibnu Khaldun, Kecerdasan Buatan (AI), Pendidikan Islam, Malakah, Atrofi Kognitif.